Sensitivity analysis using fuzzy linguistic hedges - Zamali, T.; Lazim, M. A.; Md Tap, Abu Osman (2012)
This paper proposed a new sensitivity analysis approach using the linguistic hedges in fuzzy environment. At the first place, the linguistic hedge was briefly described with emphasis on the two types, namely concentration and dilation. Afterwards the power of concentration or dilation was employed to represent the strength of the hedges. A fully linguistic variable was used to assess the entire investigation attribute in a case study. Lastly, the power of both hedge will changed into one level up or down from the basis power for testing purposes. The results show that, changing one level up or down power of the hedge cause only small variations of the performance values and the final ranking remains unchanged. Thus, it shows that our proposed approach can be utilised to derive the robust model for decision-making purposes.